2021
DOI: 10.1002/ski2.29
|View full text |Cite
|
Sign up to set email alerts
|

Can atopic eczema and psoriasis coexist? A systematic review and meta‐analysis

Abstract: Importance: Previous studies report both coexistence and mutual exclusivity of atopic eczema (AE) and psoriasis, but these have not been appraised systematically. Knowledge of such disease association throws light on disease mechanisms and may influence therapeutic choices. Objective: To summarise evidence for AE and psoriasis occurring in the same person at the same point in time. Planned primary outcome was the incidence, prevalence or risk of psoriasis or eczema. Methods: Ovid MEDLINE and Ovid Embase were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 53 publications
0
20
0
Order By: Relevance
“…Being two diseases characterized by different pathways, as PsO is predominantly Th1 while AD predominantly Th2, different authors reported a mutual exclusivity of both diseases 3, 4 . However, other observational studies have supported the coexistence of AD and PsO, reporting conflicting relationships between other Th2 and Th1 diseases 3,5 . Indeed, Cunliffe et al 3 in a systematic review found that coexistence of AD and PsO may be present, and evaluating 31 papers (20,523 individuals with PsO and 1,405,911 with AD), found that the prevalence of AD in patients with PsO has values from 0.17% to 20% with a pooled prevalence of 2%, while the prevalence of PsO in patients with AD ranged from 0.3% to 12.6% (pooled prevalence 2%) 3 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Being two diseases characterized by different pathways, as PsO is predominantly Th1 while AD predominantly Th2, different authors reported a mutual exclusivity of both diseases 3, 4 . However, other observational studies have supported the coexistence of AD and PsO, reporting conflicting relationships between other Th2 and Th1 diseases 3,5 . Indeed, Cunliffe et al 3 in a systematic review found that coexistence of AD and PsO may be present, and evaluating 31 papers (20,523 individuals with PsO and 1,405,911 with AD), found that the prevalence of AD in patients with PsO has values from 0.17% to 20% with a pooled prevalence of 2%, while the prevalence of PsO in patients with AD ranged from 0.3% to 12.6% (pooled prevalence 2%) 3 .…”
Section: Discussionmentioning
confidence: 99%
“…other observational studies have supported the coexistence of AD and PsO, reporting conflicting relationships between other Th2 and Th1 diseases. 3,5 Indeed, Cunliffe et al 3 in a systematic review found that coexistence of AD and PsO may be present, and evaluating 31 papers (20,523 individuals with PsO and 1,405,911 with AD), found that the prevalence of AD in patients with PsO has values from 0.17% to 20% with a pooled prevalence of 2%, while the prevalence of PsO in patients with AD ranged from 0.3% to 12.6% (pooled prevalence 2%). 3 Our report shows how PsO and AD may be also metachronous cutaneous diseases, that can arise in the same patients, regardless of whether undergoing systemic or topical therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This explains why bacterial infections of the skin are seldom seen in patients with psoriasis and are frequent in patients with atopic dermatitis. Although psoriasis and atopic dermatitis were supposed to be mutually exclusive (Christophers and Henseler, 1987), atopic dermatitis and psoriasis may present in the same individual, both simultaneously and consecutively, and coexistence of disease may occur at a level equal to or lower than expected (Cunliffe et al, 2021).…”
Section: Trafficking and Activation Of Th1 Cellsmentioning
confidence: 99%